Evaluation of How Integrative Oncology Services Are Valued between Hematology/Oncology Patients and Hematologists/Oncologists at a Tertiary Care Center. (12th April 2018) - Hansra, D. M.; McIntyre, K.; Ramdial, J.; Sacks, S.; Patrick, C. S.; Cutler, J.; McIntyre, B.; Feister, K.; Miller, M.; Taylor, A. K.; Farooq, F.; Mayolo, J. Antunez de; et al.
Abstract : Evidence regarding opinions on integrative modalities by patients and physicians is lacking. Methods . A survey study was conducted assessing how integrative modalities were valued among hematology/oncology patients and hematologists and oncologists at a major tertiary medical center. Results. 1008 patients and 55 physicians were surveyed. With the exception of support groups, patients valued nutrition services, exercise therapy, spiritual/religious counseling, supplement/herbal advice, support groups, music therapy, and other complimentary medicine services significantly more than physicians ( P ≤ 0.05 ) . Conclusion . With the exception of support groups, patients value integrative modalities more than physicians. Perhaps with increasing education, awareness, and acceptance by providers and traditional institutions, integrative modalities could be equally valued between patients and providers. It is possible that increased availability and utilization of integrative oncology modalities at tertiary hospital sites could improve patient satisfaction, quality of life, and other clinical endpoints.